Selective unequal-thickness thin-film filters for IR spectral region - Yaremchuk, I.Ya.; Fitio, V.M.; Bobitski, Ya.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
A new five-layer structure of the dielectric interference filter for the infra-red region of spectrum is investigated. The main spectral parameters of such a narrow-band filter are determined. The dependence of the transmission band half-width on the thickness of a dividing layer in this system is investigated. It is shown that, in the case of the application of PbTe, GeTe, and SnTe layers with a given thickness; their number can be limited to five at providing the necessary selectivity of the filter: practically the 100-% transmission at the resonance frequency and 0.005 % outside the transmission band.